CD8+ T Cells in Leishmania Infections: Friends or Foes? - Stager, Simona; Rafati, Sima (Frontiers in Immunology, 2012)
Host protection against several intracellular pathogens requires the induction of CD8+ T cell responses. CD8+ T cells are potent effector cells that can produce high amounts of pro-inflammatory cytokines and kill infected target cells efficiently. However, a protective role for CD8+ T cells during Leishmania infections is still controversial and largely depends on the infection model. In this review, we discuss the role of CD8+ T cells during various types of Leishmania infections, following vaccination, and as potential immunotherapeutic targets.